Efficacy of dural venous sinus stenting in treating idiopathic intracranial hypertension with acute vision loss. Issue 1 (February 2022) - Zehri, Aqib H; Lee, Katriel E; Kartchner, Jeff; Arnel, Madison; Martin, Timothy; Wolfe, Stacey Q; Fargen, Kyle M
Introduction: Dural venous sinus stenting (VSS) is an effective, durable treatment for patients with idiopathic intracranial hypertension (IIH) due to underlying venous sinus stenosis. However, the use of venous sinus stenting to treat IIH with acute vision loss has rarely been described. Methods: A retrospective chart analysis identified patients who received VSS for fulminant IIH, defined as acute (< 8 weeks) visual field loss to within the central 5° and/or a decrease in visual acuity to less than or equal to 20/50 in either eye in the presence of papilledema. Results: Ten patients were identified with average patient age of 31.0 years, and all except one were female. Mean body mass index was 41.2 kg/m 2 . All patients presented with vision loss and some with headache and tinnitus. The average trans-stenotic gradient pre-stenting was 28.7 mmHg (range 9–62 mmHg). All patients had diminished or resolved venous gradients immediately following the procedure. At mean follow-up of 60.5 weeks, 100% had improvements in papilledema, 80.0% had subjective vision improvement, 55.6% had headache improvement and 87.5% had tinnitus improvement. 90.0% had stable or improved visual acuity in both eyes with a mean post-stenting Snellen acuity of 20/30 and an average gain of 3 lines Snellen acuity post-stenting (95% confidence intervals 0.1185–0.4286, p  = 0.0018). Two patients (20.0%) required further surgical treatment (cerebrospinal shunting and/or stenting) after their first stenting procedure. Conclusions: This series suggests that VSS is feasible in patients presenting with IIH and acute vision loss with a fairly low complication rate and satisfactory clinical outcomes.